Hubungan Antara Pemeriksaan Laju Endap Darah dan Tes Cepat Tuberkulosis IgG/IgM - Widodo, Widodo; Afriansah, Roni; Triyono, Damas (Poltekkes Kemenkes Semarang, 2025)
Mycobacterium tuberculosis is an acid-fast bacteria that causes pulmonary tuberculosis (TB) is an infectious disease that is a priority health problem in developing countries including Indonesia. Fast and accurate examination is very important in diagnosing tuberculosis. Tuberculosis examination has several methods that are not commonly applied, namely the Immunochromatography test (ICT) examination. This study is a non-experimental study with a survey method without intervention that is descriptive analytical. The purpose of the study was to see the relationship between the examination of the Erythrocyte Sedimentation Rate and the Rapid Tuberculosis IgG / IgM Test. The results obtained that the LED results of 8 samples were normal and 17 samples were abnormal, while the ICT test for IgG examination of all samples was negative, IgM 24 samples were negative and 1 sample was positive. The results of the Chi square statistical test obtained an Î± value of 0.618 so that it can be concluded that there is no relationship between the LED value and the results of the IgG and IgM tuberculosis tests.